VARIATION OF MICROBIAL ACTIVITY AND PERMEABILITY OF COMPACTED CLAYS PERMEATED WITH LEACHATE - Ozcoban, Mehmet Sukru; Durak, Sevgi Gunes; Ormanci-Acar, Turkan; Turkoglu-Demirkol, Guler; Ovez, Suleyman; Tufekci, Nese (PARLAR SCIENTIFIC PUBLICATIONS (P S P), 2019)
In this paper, the effects of microbial activity on permeability and the treatment capability of compacted clay soil have been determined. Soil samples and leachates were obtained from the Sile-Komiirctioda Organized Landfill Area on the Asia side of Istanbul. Standard and modified proctor compaction tests were applied to the clay soil. The leachate sample has been passed through the reactors prepared with the clay samples taken from the same facility and subjected to the standard and modified compaction tests. The effects of microbial activity on the permeability of compacted clay soil samples have been analyzed. Microbial activities of influent and efluent samples have been also measured to determine the treatment capability of the compacted clay soil. Microbial activities i.e., microorganisms including total heterotrophic bacteria, fecal coliforms, total coliforms, fecal streptococci and fungi have been monitored and tested. Based on the findings, initially some decrease has been observed in the clay permeability associated with the contamination. The suspended solid matters of leachate have filled the spaces between the particles and the clay soil. The growth of microorganisms inside the soil pores caused pore clogging which have led to a decrease in the permeability. In the length of time, these results show that leachates may cause increase in the permeability.
Keywords: Permeability; leachate; compacted clay soil; removal efficiency; microbial activity; HYDRAULIC CONDUCTIVITY; LANDFILL LEACHATE; REMOVAL; LINERS; Environmental Sciences & Ecology